Cembranoid constituents from lobophytum crassum - Van Minh, Chau; Xuan Cuong, Nguyen; Phuong Thao, Nguyen; Thu Thuy, Dinh Thi; Ngoc, Ninh Thi; Van Thanh, Nguyen; Hoai Nam, Nguyen; Young Ho, Kim; Van Kiem, Phan (Vietnam Journal of Chemistry, 2015)
Five cembranoids, 2,16:7S,8S-diepoxy-1,3,11,15-cembratetraene (1), 7S,8S-epoxy-1,3,11-cembratriene-16-oic acid methyl ester (2), (1R,4R,2E,7E,11E)-cembra-2,7,11-triene-4-ol (3), (2S,7S,8S)-sarcophine (4), and (2S,7S,8S)-sarcophytoxide (5), were isolated from the methanol extract of the soft coral Lobophytum crassum by using various chromatographic methods. Their structures were elucidated by 1D and 2D-NMR experiments and comparison of their NMR data with reported values. Compounds 1 and 3 were isolated from L. crassum for the first time.